Effects of Quinoa Flour on Wheat Dough Quality, Baking Quality, and in vitro Starch Digestibility of the Crispy Biscuits - Ma, Yanrong; Wu, Daying; Guo, Lei; Yao, Youhua; Yao, Xiaohua; Wang, Zhonghua; Wu, Kunlun; Cao, Xinyou; Gao, Xin (Frontiers in Nutrition, 2022)
Quinoa is a pseudo-cereal which has excellent nutritional and functional properties due to its high content of nutrients, such as polyphenols and flavonoids, and therefore quinoa serves as an excellent supplement to make healthy and functional foods. The present study was aimed to evaluate the quality characteristics of wheat doughs and crispy biscuits supplemented with different amount of quinoa flour. The results showed that when more wheat flour was substituted by quinoa flour, proportion of unextractable polymeric protein to the total polymeric protein (UPP%) of the reconstituted doughs decreased and the gluten network structure was destroyed at a certain substitution level. The content of B-type starch and the gelatinization temperature of the reconstituted flours increased. The storage modulus, loss modulus, development time, and stability time of the dough increased as well. Moreover, hardness and toughness of the formulated crispy biscuits significantly decreased. Analyses suggested that starch digestibility was reduced and resistant starch content increased significantly. Taken together, quinoa flour improved dough rheological properties, enhanced the textural properties, and increased resistant starch content in crispy biscuits, thus adding to high nutritional value.